A cylindrical self-consistent modelling of vegetal wools thermal conductivity. (30th January 2020) - Piégay, Clément; Glé, Philippe; Gourdon, Emmanuel; Gourlay, Etienne
Highlights: Thermal conductivity modelling for fibrous insulating materials. Cylindrical self-consistent modelling of vegetal wools thermal conductivity. Biphasic cylindrical inclusion as representative elementary volume. Experimental characterization of vegetal wools thermal performances. Parametric analysis to explore the optimum ranges of vegetal wools thermal conductivity. Abstract: In recent years, the fight against climate change has come to the fore. In this scope, the use of vegetal wools, which can store carbon dioxide, is particularly relevant for developing greenbuilding solutions. Moreover, considering their high porosity levels, the thermal performances of these materials can compete with conventional insulators ones. These performances are related to the microscale vegetal fibres specificities that are used in the wool manufacturing process. So, a self-consistent modelling approach is developed in order to model the vegetal wools thermal properties as a function of their microscale parameters. To do that, a simplifying assumption assimilates the fibres to a representative elementary volume based on a biphasic (including solid and fluid phases) cylindrical inclusion. This model has been validated in the specific case of a flow perpendicular to the fibres by comparison with experimental characterisations performed on four materials in real hygrothermal conditions and with data from literature. Thanks to a parametric analysis, it is finally shown that for high porosity values ( > 95 % ), vegetal wools thermal properties present interesting values regardless of the solid phase thermal conductivity.